A industria de papel e cartón na Unión Europea : un modelo cuantitativo - Chas Amil, María Luisa (1998)
"The main objective of this study is to develop a model for the paper and paperboard industry in order to predict prices and quantities demanded and supplied in the European Union countries. As a prerequisite to modeling, it is necessary to understand the development of the technologies and products involved as well as the environmental problems related with paper and paperboard manufacturing. Moreover, a description of the industry situation in the European Union is also presented. The model used has been PELPS III (Price Endogenous Linear Programming System). PELPS III is a spatial equilibrium model based on econometric methods and mathematical programming. It has two distinct computational phases: a static and dynamic phase. The solution of the static phase is obtained by a linear programming problem which describes the state of the sector at a given point in time. By maximizing the objective function (the net social pay-off), it gives the equilibrium quantities and the corresponding prices that clear all markets at a given point. In its dynamic phase, PELPS III breaks down a multi-period spatial equilibrium problem into a sequence of problems. Thus, the dynamic phase is a succession of static phases, one for each period of forecast.The model is applied to simulate the paper and paperboard industry behavior in the European Union for the period 1987-1992 and to make forecasts for the period 1996-2005."